IN VITRO COMPARISON OF OSTEOGENIC DIFFERENTIATION POTENTIAL BETWEEN BONE MARROW STEM CELLS AND ADIPOSE TISSUE MESENCHYMAL STEM CELLS : A SYSTEMATIC REVIEW - Prima Rizky Oktari (Journal of Global Pharma Technology, 2017)
AbstractIntroduction. Bone tissue engineering (BTE) becomes a promising issue to improve bone defect repair. Stem cells are the first choice in BTE due to the ability of selfrenewal and multi-lineage differentiation. Adipose tissue (AT) is another alternative source that can be obtained by a less invasive method and in larger quantities than bone marrow. Materials and Method. Literature search was conducted using several search engines, such as Cochrane, Scopus, PubMed, EBSCO, and Google Scholar. Studies were screened for inclusion and exclusion criteria.. This review used all In vitro experimental comparison of Mesenchymal Stem Cells (MSCs) derived from adipose tissue and bone marrow. We compared osteogenic differentiation potential between these MSCs. The group of comparison is divided into two sub groups, first group is the comparison among the animal MSCs, and the second group is the comparison among the human MSCsResult and Discussion. From three invitro study and one animal study that compares osteogenic activity of MSC from adipose and MSC from bone marrow, Most of the study shows the osteoblastic differentiation of ATMSCs as demonstrated by AP staining was less than that of the BMMSCs. The amount of matrix mineralization shown by Von Kossa staining also showed statistical differences between the two MSCs.Conclusion. ATMSC have differentiation potential similar to that of BMMSC, ATMSC may be a better source for tissue repair in the respect of their abundance and accessibility.Keyword: Osteogenic differentiation, Mesenchymal Stem Cells, Adipose Tissue Mesenchymal Stem Cells.